Cutaneous leishmaniasis treatment and therapeutic outcomes in special populations: A collaborative retrospective study. - Maria Del Mar Castro; Joelle Rode; Paulo R L Machado; Alejandro Llanos-Cuentas; Marcia Hueb; Gláucia Cota; Isis Valentina Rojas; Yenifer Orobio; Oscar Oviedo Sarmiento; Ernesto Rojas; Juliana Quintero; Maria Inês Fernandes Pimentel; et al. (PLoS Neglected Tropical Diseases, 2023)
Background Treatment guidance for children and older adult patients affected by cutaneous leishmaniasis (CL) is unclear due to limited representation of these groups in clinical trials. Methods We conducted a collaborative retrospective study to describe the effectiveness and safety of antileishmanial treatments in children ≤ 10 and adults ≥ 60 years of age, treated between 2014 and 2018 in ten CL referral centers in Latin America. Results 2,037 clinical records were assessed for eligibility. Of them, the main reason for non-inclusion was lack of data on treatment follow-up and therapeutic response (182/242, 75% of children and 179/468, 38% of adults). Data on 1,325 eligible CL patients (736 children and 589 older adults) were analyzed. In both age groups, disease presentation was mild, with a median number of lesions of one (IQR: 1-2) and median lesion diameter of less than 3 cm. Less than 50% of the patients had data for two or more follow-up visits post-treatment (being only 28% in pediatric patients). Systemic antimonials were the most common monotherapy regimen in both age groups (590/736, 80.2% of children and 308/589, 52.3% of older adults) with overall cure rates of 54.6% (95% CI: 50.5-58.6%) and 68.2% (95% CI: 62.6-73.4%), respectively. Other treatments used include miltefosine, amphotericin B, intralesional antimonials, and pentamidine. Adverse reactions related to the main treatment were experienced in 11.9% (86/722) of children versus 38.4% (206/537) of older adults. Most adverse reactions were of mild intensity. Conclusion Our findings support the need for greater availability and use of alternatives to systemic antimonials, particularly local therapies, and development of strategies to improve patient follow-up across the region, with special attention to pediatric populations.